Remarks at the Climate Ambition Summit 2020 - Malpass, David (World Bank, Washington, DC, 2020)
World Bank Group President David Malpass spoke about the Climate change, poverty, and inequality–defining issues of our age. The global poor often suffer the most from climate events, including flooding, droughts and food insecurity. The World Bank Group is the biggest multilateral funder of climate investments in developing countries. Over the next five years, the Bank intends to go further, targeting thirty-five percent climate co-benefits on average across the World Bank Group. For IBRD and IDA, fifty percent of this climate finance will support adaptation and resilience. The Bank will support the Paris accord alignment by helping developing countries to achieve their NDCs, end their reliance on coal, and transition to lower-carbon, climate-resilient economies. He discussed the Coronavirus (COVID-19) response, targeting investment and policy financing that will help support a green, inclusive and resilient recovery. We cannot succeed in helping countries reduce poverty without rising to the challenges of climate change.